49.9k views
3 votes
Use an Addition or Subtraction Formula to find the exact value of the expression, as demonstrated in Example 1. cos 41π 12.

User Xiduzo
by
5.3k points

1 Answer

1 vote

Answer:
(√(6)-√(2))/(2)

Explanation:

We apply the formula
\cos(x+y)=\cos(x)\cos(y)-\sin(x)\sin(y).

Note that
\cos((41)/(12)\pi)=\cos(((36)/(12)+(7)/(12))\pi)=\cos(3\pi + (7)/(12))\pi). Take
x=3\pi and
y=(7)/(12)\pi in the formula above to get


\cos((41)/(12)\pi)=\cos(3\pi)\cos((7)/(12)\pi)-\sin(3\pi)\sin((7)/(12)\pi)=(-1)\cdot \cos((7)/(12)\pi)-0\cdot\sin((7)/(12)\pi)=-\cos((7)/(12)\pi)

Then the value of this expression is
-\cos((7)/(12)\pi)

We can use the cosine addition formula again to simplify further. Decompose the fraction in the argument as:


\cos((7)/(12)\pi)=\cos(((3)/(12)+(4)/(12))\pi)=\cos(((1)/(4)\pi + (1)/(3))\pi)

Applying the formula with
x=(1)/(4)\pi and
y=(1)/(3)\pi we obtain


\cos((7)/(12)\pi)=\cos((1)/(4)\pi)\cos((1)/(3)\pi)-\sin((1)/(4)\pi)\sin((1)/(3)\pi)=(√(2))/(2)\cdot(1)/(2) -(√(2))/(2)\cdot(√(3))/(2)=(√(2)-√(6))/(2)

We conclude that this expression has the value
-(√(2)-√(6))/(2)=(√(6)-√(2))/(2)

User Adrianmcmenamin
by
4.2k points